Fulvio Papi lettore di poesia del Novecento (il caso di Vittorio Sereni) - Marinoni, Manuele (L'ospite ingrato, 2021)
The study is an investigation into some peculiarities of reading poetry by an important exponent of Italian philosophy, Fulvio Papi. Linked, also biographically, to Vittorio Sereni, for years Papi exercised his hermeneutic acumen on the poet from Luino. Fundamental, in this sense, is the essay published in 1992 in La parola incantata e altri saggi di filosofia dell’arte. In my study I have given ample space to the reasons of temporality, of subjectivity and of nothingness, which the philosopher’s reading mainly focuses on.